Spectral variation in Brillouin-Raman fiber laser - Zamzuri A.K.; Mahdi M.A.; Al-Mansoori M.H.; Samsuri N.M.; Ahmad A.; Mohamad R.; Yaakob M.S. (2023)
This article discusses the optical-SNR variation of Stokes lines in BRFL. This variation is partly attributed to the cavity modes interaction through intraline-FWM residing the same spectralwidth. The worst OSNR is obtained at 650mW RPP and 1555nm BPW. The improvement is obtained for the RPP beyond 650mW. 2009 OSA/ACP.